MODEL SISTEM PEMBAYARAN JASA LINGKUNGAN DALAM KAITANNYA DENGAN KONSERVASI SUMBERDAYA AIR DAN LAHAN: STUDI KASUS PADA BATANG ANAI SUMATERA BARAT (JURNAL ECONOMICA : Research of Economic And Economic Education, 2012)
The purpose of this study is to see how the payment system model of environmental services as upstream-downstream transfer mechanism in the management of water resources and land in the watershed and Batang Batang Anai Kuranji. This study is the economic perspective of water resources have been developed by economists who joined the stream of new institutional economics (new instituional economics).Analysis using the new institutional economics approaches in the analysis that emphasizes two perspectives namely joint action theory in collective choice theory and games theory. Analytical equipment used is econometric analysis, dynamic analysis and efficiency analysis. This study found that 1) West Sumatra has the potential water resources are more than sufficient to meet the need for the use of water for irrigation, drinking water and for industrial use and use for power generation. 2) In the Batang Anai watershed areas, water resource use is dominated by irrigation water users, especially in Pariaman District, while the use of the water is not there. 3) water in Batang Anai River Basin has not been streamed to users who value efficient that water usage not in accordance with the principle of efficiency. 4) The total area of watershed Batang Anai has decreased from year to year, which affects the availability of water is declining. 5) The competent authorities in managing the watershed Batang Anai is PSDA West Sumatra province of Sumatra and Central River Region V and Watershed Management Board Agam-Kuantan. 6) In making the benefits of water resources in the watershed currently Batang Anai, industrial users are not there, which is the dominant irrigation and household water users. 7) Number of total water use of population catchment area totaling 6,439,233 Batang Anai is 6,439,233 m3/tahun/person, this only amounted to 5.04% of the existing availability of water in the watershed Batang Anai that amounted in 2011 was 127, 38 million m3/year. Batang Anai River Basin water users the greatest population in the district was 1,332,183 m3/year Means Batang Anai River Basin water use for household purposes is still quite small. 8) Use Batang Anai River Basin water for irrigation purposes with irrigated area reached 13,604 ha, with the need for the flow of water is equal to 10.15 m3, the water requirements for wetland that will be irrigated by water is much Batang Anai 16324.8 m3/ha. The number is certainly very small compared to the availability of water in the watershed Batang Anai. That is, the availability of water for irrigation purposes is still considerable potential, it flows off to the sea is still very large